Contribution of Recycling of Municipal Solid Waste to the Social Inclusion in Brazil. (6th March 2013) - Lino, F. A. M.; Ismail, K. A. R.
Abstract : This paper proposes the selective collection and recycling as alternative ways to promote the social inclusion in Brazil and help the country to eradicate extreme poverty and misery and achieve the first of the Millennium Development Goals (MDG1) of the UN. This work is based on the data from a Brazilian metropolitan city of Campinas and is extended to Brazil. The results show that the municipality of Campinas collects monthly 8000 tons of recyclables which if recycled can avail jobs to nearly 13, 000 waste collectors with a minimum national salary of R 622/month or alternatively can create 40, 280 Family Grants of R 200/month. In Brazil, the collected recyclables potential is about 2.4 million tons per month which can avail jobs to 2, 350945 waste collectors or alternatively create about 7.3 millions Family Grants.